Mindfulness-Based Cognitive Therapy on a Postpartum Woman with HIV and Depression: A Case Report - Fadilla Rifky Hasan; Susatyo Yuwono (Faculty of Psychology, Universitas Gadjah Mada, 2026)
Human Immunodeficiency Virus (HIV) infection remains a complex psychological and social challenge, particularly for women in the postpartum period. This case study aimed to illustrate the effectiveness of a mindfulness-based cognitive therapy (MBCT) within the biopsychosocial framework in reducing psychological distress in an HIV-positive housewife who had been diagnosed with a depressive episode. The research design was a single-case intervention study involving a 36-year-old woman who was undergoing both antiretroviral and psychiatric treatment. Data were gathered through in-depth interviews, clinical observation, and measurement using the Beck Depression Inventory. The intervention was delivered in eight sessions, focusing on mindfulness exercises, breathing awareness, cognitive restructuring, and reflective journaling. The results showed a reduction in depressive symptoms from moderate to mild, accompanied by improvements in emotional stability, self-awareness, and social functioning. The participant could resume daily activities, establish positive communication with her partner, and maintain treatment adherence. These findings suggest that mindfulness-based cognitive therapy delivered within a biopsychosocial framework can improve psychological well-being and interpersonal functioning in women living with HIV. A holistic and culturally sensitive approach is essential to support their recovery and mental resilience.